Pelatihan Uji Kompetensi Keahlian Pada Siswa Kelas XII SMK NWDI Renco - Putra, Yupi Kuspandi; Hariman Bahtiar; Yahya; Muhammad Saiful; Muh. Adrian Juniarta Hidayat; Fathurrahman; Amri Muliawan Nur; L.M.Samsu; Nurhidayati; Aswian Editri Sutriandi (Universitas Hamzanwadi, 2024)
This service aims to help students improve their readiness and skills in completing the Skills Competency Test in the field of Computer and Network Engineering. The National Examination is no longer a determinant of graduation based on government regulations through the Ministry of Education and Culture which regulates policies and criteria for student graduation. Even though they no longer require national test scores, schools have full power in determining the school graduation requirements for their students, but these requirements must be in accordance with the circular issued by the Minister of Education and Culture. The target of this activity is class XII students at NWDI Renco Vocational School who are the main partners. The target and output of this activity is the development of skills in working on skills competency test questions that are skills in nature. The method used is Participatory Learning and Action (PLA). This activity is carried out by providing practical knowledge and skills. With this skills competency training, especially in the field of Computer and Network Engineering, it is hoped that it can help students prepare for skills competency tests to get maximum results and improve student competency. Keywords : Skill Competency, Vocational School, Computer and Network Engineering, Participatory Learning and Action